The burning of the witches of 1507. Notes on a historical enigma - Aranda Fernández-Cañadas, Eudaldo (Huarte de San Juan. Geografía e Historia, 2010)
This article aims to corroborate the information provided by Juan Antonio Llorente in his Anales de la Inquisición en España regarding the burning of more than thirty women as witches in Biscay in 1507. Three documentary sources were used: Pedro de Torres’ Cronicón, Doctor Isidoro de San Vicente’s Memorial (1610) and a document on the trial of faith against María de San Juan (1508), who was condemned as a witch. These testimonies would seem to prove the existence of this trial, which was conducted by the Inquisition of Durango and more specifically the inquisitor Juan Martínez de Frías.